“A podcast would be fun!”: The fetishization of digital writing projects - Hotson, Brian; Bell, Stevie (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
While digital writing projects (DWPs) like podcasts, videos, and infographics are rigorous sites of scholarly knowledge production, the growth in their popularity as classroom assignments often has more to do with a sense that these are “fun” assignments. Horner, Selfe, and Lockridge (2015) describe such dismissive attitudes using the term fetishization. When DWPs are fetishized by students and faculty, they are celebrated while being dismissed as pedestrian fads. Ultimately, fetishization decreases the amount of support offered by faculty, the effort invested by students, as well as the demand (and budget) for learning service support. This means that disparities between students (including access to technologies, digital literacies, and “normative” abilities) are exaggerated. In this paper, we illuminate four interconnected drivers of fetishization that obscure the realities of DWPs—the myth of digital natives, assumptions about tool-content division, faith in digital tool neutrality, and idealizations of the web. Like all teaching approaches, thoughtful instructional design and learning supports are required for DWPs to create effective, equitable, safe, inclusive, and accessible learning opportunities. This paper enhances writing instructors’ and tutors’ ability to challenge fetishized perspectives of DWPs in their work with faculty and students alike.